Rapid DNA from a disaster victim identification perspective: Is it a game changer?. (May 2022) - Bowman, Z.; Daniel, R.; Gerostamoulos, D.; Woodford, N.; Hartman, D.
Abstract: As an emerging technology, Rapid DNA has demonstrated its utility for law enforcement in the provision of DNA profiling data at the point of arrest, often not requiring analyst review of the profiles generated. Recently, efforts have centred on the evaluation of Rapid DNA (without analyst review) and modified Rapid DNA (requiring review by a trained analyst) for application to crime scene samples. In a broader forensic context, however, another application for Rapid DNA is its use to process post-mortem samples to assist with the identification of deceased persons; and while gaps in our knowledge remain as to how Rapid DNA instruments perform with these sample types (often compromised with regards to their yield and quality of DNA), they have been successfully deployed in the field to assist in the identification of disaster victims (as exemplified during the 2018 Californian wildfire). This review aims to provide the current research landscape for the forensic application of Rapid DNA as an emerging technology from a Disaster Victim Identification perspective. Highlights: Rapid DNA offers the possibility to take DNA profiling out of the laboratory. Commercial instruments are reliable for processing buccal samples. Rapid DNA could assist in DVI by reducing profiling time and simplifying logistics. Benefit in DVI will depend on operational and jurisdictional circumstances.